Optimization of the Standalone Hybrid Energy Storage System in The All-Electric Seabus Power System Based on Pulsed Propulsion Load Prediction - Mohammad Yusqi Shoubil Haq; Vita Lystianingrum; Agoes Santoso (International Journal of Marine Engineering Innovation and Research, 2025)
In marine applications, the energy storage system (ESS) functions as the primary energy supply for fully electric propulsion vessels. During variable operation conditions involving pulsed propulsion load, the ESS employing monotype topologies are often oversized and can damage the cells. This study proposes a hybrid energy storage system (HESS) for an all-electric Seabus with a 10-year operational lifespan, with the objective of optimizing the storage system size to ensure longer operation than 72 minutes at a speed of 30 knots under variable conditions. The impact of the HESS system on installation cost and weight was thoroughly investigated. Some HESS configurations are presented, utilizing Lithium Iron Phosphate (LFP) as the high-energy (HE) cell and supercapacitors, Lithium Ion Capacitor (LIC), and Lithium Titanium Oxide (LTO) as three alternatives of the high-power (HP) cell. The HESS design predates a parallel full-active configuration with a rule-based energy management method that utilizes cut-off power between HE and HP cells. In this specific case, the LFP-LTO configuration is the optimal HESS design rather than the LFP-SC and LFP-LIC configurations, meeting all established optimization criteria and weight limitations. The study demonstrates that the HESS configuration can achieve 120 minutes of operation, which is 67% longer than the operation time of previous Seabus operations.